2019
DOI: 10.1002/advs.201900576
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Hierarchical Co–Fe Oxyphosphide Microtubes for Electrocatalytic Overall Water Splitting

Abstract: Development of efficient electrocatalysts is a crucial requirement to build water splitting systems for the production of clean and sustainable fuels. This goal could be achieved by fine‐tuning the composition and structure of the electrocatalytic materials. Here, a facile self‐templated synthetic strategy is developed for the fabrication of hierarchical Co–Fe oxyphosphide microtubes (MTs). Fe‐based metal–organic compound microrods are first synthesized as the self‐sacrificing template. Afterward, the Fe‐based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(121 citation statements)
references
References 47 publications
0
119
1
1
Order By: Relevance
“…As‐prepared catalysts with high surface area/electrochemical surface area (ECSA) are always desired . Exfoliation of nanosheets, rationally design of materials with hierarchical or hollow structure are mainstream approaches to enlarge the ECSA via structural engineering. Wang et al.…”
Section: Common Strategies To Improve Electrocatalytic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…As‐prepared catalysts with high surface area/electrochemical surface area (ECSA) are always desired . Exfoliation of nanosheets, rationally design of materials with hierarchical or hollow structure are mainstream approaches to enlarge the ECSA via structural engineering. Wang et al.…”
Section: Common Strategies To Improve Electrocatalytic Performancementioning
confidence: 99%
“…As-prepared catalysts with high surface area/electrochemical surface area (ECSA) are always desired. [122] Exfoliation of nanosheets, [123] rationally design of materials with hierarchical [124] or hollow structure [101b,125] are mainstream approaches to enlarge the ECSA via structural engineering. Wang et al reported the partial exfoliation and modulation of CoFe-LDH with multi-vacancies by plasma treatment to achieve boosted OER activity.…”
Section: Structural Engineeringmentioning
confidence: 99%
“…However, those sustainable energy sources are usually intermittent with a time gap between the supply and demand 3. As a result, energy conversion and storage technologies, such as water electrolysis which converts electric energies generated from solar and wind power into hydrogen fuels,4,5 rechargeable metal‐air batteries which possess exceptionally high energy density and exhibit low cost, environmental benignity, and safety,6,7 and reversible fuel cells (RFCs) which can also produce hydrogen fuel via electrochemical process,8 are hence greatly required to achieve a sustainable energy landscape. Governed by the electrochemical reactions, the advancement of those energy conversion and storage systems is significantly impeded by the sluggish kinetics of the oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and hydrogen evolution reaction (HER) 9–15.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we put primary focus on these non‐noble‐metal‐based electrocatalysts in this review. To overcome the high overpotential of the OER, numerous non‐noble‐metal‐based electrocatalysts have been developed, including metals/alloys,23,24 oxides,25–31 hydroxides,32–37 chalcogenides,38–42 phosphides,5,43,44 phosphates/borates,19,45,46 borides,47 nitrites,48,49 and other compounds 50,51…”
Section: Introductionmentioning
confidence: 99%
“…The Nyquist plot was recorded with the frequency ranging from 1 to 10 5 Hz. The electrochemical double‐layer capacitance and electrochemical active surface area were calculated with a series of cyclic voltammetry (CV) measurements at different scan rates between 1.11 and 1.26 V vs. RHE …”
Section: Methodsmentioning
confidence: 99%